If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) + -10 = 66 + -5x Reorder the terms: 3(4 + x) + -10 = 66 + -5x (4 * 3 + x * 3) + -10 = 66 + -5x (12 + 3x) + -10 = 66 + -5x Reorder the terms: 12 + -10 + 3x = 66 + -5x Combine like terms: 12 + -10 = 2 2 + 3x = 66 + -5x Solving 2 + 3x = 66 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 2 + 3x + 5x = 66 + -5x + 5x Combine like terms: 3x + 5x = 8x 2 + 8x = 66 + -5x + 5x Combine like terms: -5x + 5x = 0 2 + 8x = 66 + 0 2 + 8x = 66 Add '-2' to each side of the equation. 2 + -2 + 8x = 66 + -2 Combine like terms: 2 + -2 = 0 0 + 8x = 66 + -2 8x = 66 + -2 Combine like terms: 66 + -2 = 64 8x = 64 Divide each side by '8'. x = 8 Simplifying x = 8
| .33(5x+12)+.33=-1 | | .5(x-6)=19 | | x(2)=x+6 | | (M*4)*3= | | 5(3x-4)=-15 | | -x-2x=-7 | | -10.4x=72.8 | | 7+3x+4=20 | | X*5xX*3= | | 4y^2-36=0 | | 2t=-30 | | 0.04+0.07(6000-x)=360 | | 6-3y=9 | | 8(3-x)=3x+2 | | -3y=3 | | -11-8x=7(x+2) | | 75=15+18 | | 12z^2+z=0 | | 1.5t+6=17 | | 3(2x+4)=9 | | t^2-4z^2=0 | | 5(2x-3)=8 | | -8(2b+3)+(17b-7)=0 | | x^2+5x-729=0 | | 5(3x-2)=3(x+2) | | C=12500+2.75 | | 16k^2-81=0 | | 3x^2+21x+18=0 | | 2x^2-10x=7 | | 4x-5=355 | | 4(2x-3)=3(x+4) | | C=12500+n |